Revision of Ascra with proposition of the bifida species group and description of two new species (Hemiptera: Pentatomidae: Edessinae) - Santos, Bianca Tamires Silva Dos; Silva, Valeria Juliete Da; Fernandes, Jose Antonio Marin (Zootaxa, 2015)
Edessa is comprised of six subgenera, Aceratodes, Ascra, Dorypleura, Edessa, Hypoxys and Pygoda. Ascra is here elevated to genus status based on characteristics of the male and female genitalia and the gibbous pronotum. This genus is comprised of eight species previously placed in Edessa—E. bifida, E. cordifera, E. petersii, E. abdita, E. championi, E. privata, E. conspersa and E. morbosa, as well as six new species. The genus Ascra was further divided into two groups of species bifida and privata separated by a different pattern of punctuation on body and pygophore. Here we present only the bifida species group formed by A. bifida, A. cordifera, A. petersii, A. abdita, and A. championi, as well as two new species—A. vluteum and A. flavoscutellata. Lectotypes of Aceratodes sigillatus, Edessa abdita, E. championi, E. cornuta, E. densata and E. petersii are designated. Aceratodes sigillatus, Edessa cornuta, E. densata, E. picata, and E. florida are considered junior synonyms of A. bifida. Interestingly, some species of this genus are considered edible in Mexico.